PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN DARING MATA PELAJARAN FIQIH DI MI BUSTANUL ULUM KOTA BATU - Novadita Agustin Damayanti; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The use of audio-visual media in online learning for Fiqh subjects is a new thing that has been experienced at MI Bustanul Ulum Batu City. The focus of the research discusses the online learning process, the use of audio-visual media for online learning, and the inhibiting and supporting factors for the use of audio-visual media in online learning for Fiqh subjects. The researcher uses a qualitative approach with the type of case study research. The collection technique uses interviews, observation, and documentation. Based on the results of this study the researchers suggested that the online learning process used teaching materials, namely worksheets and worksheets. Then to deliver the material using learning videos, zoom, and google forms. The use of audiovisuals is like a learning video by the teacher sending selected material that is difficult for students to understand. The teacher also uses zoom to deliver the material directly. Then the use of google forms makes it easier for students to work on questions online. Optimal use of audio-visual media is used in the online learning process. The inhibiting factor for the use of audio-visual media is constrained by the unstable network, mobile memory is full, facilities are inadequate. While the supporting factors are good facilities, a smooth internet network, and always get support from parents.Kata Kunci: Online Learning, Audio Visual Media, Fiqh Lessons